Analysis of Change Management at UNJ from PTN BLU to PTNBH - Nanda Cista Pradipta; Ipah Ema Jumiati; Tora Akadira (Universitas Trunodjoyo Madura, 2026)
The institutional transformation into a State-Owned Legal Entity University (PTNBH) is a strategic step for the Jakarta State University (UNJ) in strengthening its autonomy and competitiveness at the national and global levels. However, in the transformation process, there are a number of major issues that pose challenges, such as the suboptimal relevance of graduate competencies, the utilization of research results that have not had a significant impact on society, suboptimal asset management, and an information system that is not yet fully integrated. This study aims to identify change management strategies and internal and external factors that influence the change management strategies implemented by Jakarta State University in facing the challenges of transformation into a PTNBH. This study uses a qualitative approach with an evaluative design. Research data was obtained through in-depth interviews, documentation studies, and observations of change management at UNJ in the process of transforming into a PTNBH. The results of this study are expected to provide an overview of change management strategies and internal and external factors that influence the change management strategies implemented by Jakarta State University in facing the challenges of transforming into a PTNBH.